A study on factors that influence students’ decision in using Islamic banking system / Noor Wahidah Mat Daud and Nurul Izzah Hamzah - Mat Daud, Wahidah; Hamzah, Nurul Izzah (Faculty of Business and Management, 2013)
The purpose of this study is to determine the factors that influence student’s decision in using Islamic banking system. The respondents for this study are among 140 finance students whose currently in semester 4 at UiTM Kampus Bandaraya Melaka. This study takes into consideration about students’ knowledge and education, bank’ service quality, bank’s product attributes as well as bank’s image and reputation as the independent variables and students’ decision in using Islamic banking system as the dependent variable. This study is a quantitative research whereby Statistical Package for the Social Sciences (SPSS) is used to analyse the results. Next, the data collected is analysed by using frequency, descriptive analysis, reliability, Pearson’s correlation analysis and multiple regression analysis in order to achieve the research objectives. R-square and F-test are used to identify the factors that influence students’ decision in using Islamic banking system where 56.2% of dependent variable is explained by the independent variables and this model is accepted. Besides that, there are hypotheses that have been accepted and rejected by using Pearson’s correlation analysis in order to examine the relationship between independent variables and dependent variable. By using multiple regression, it can be concluded that bank’s image and reputation is the most significant factor that influence students’ decision in using Islamic banking system.